Early acquisition of cytolytic function and transcriptional changes in a primary CD8+ T-cell response in vivo. - Chiu, C; Heaps, A; Cerundolo, V; Mcmichael, A; Bangham, C; Callan, M (2007)
Functional studies show that programming of CD8+ T cells occurs early after initial antigen encounter within as little as 2 hours. To define the molecular basis of these events, we transferred TCR transgenic T cells from F5 Rag-/- mice into naive recipients and stimulated them with recombinant vaccinia expressing the immunodominant influenza epitope NP366-374. Transcription in epitope-specific cytotoxic T lymphocytes (CTLs) was analyzed using Affymetrix 430 2.0 GeneChips and quantitative polymerase chain reaction (PCR). We demonstrated an early transcriptional burst with the greatest number of genes reaching peak expression 12 hours after stimulation. Using in vivo cytotoxicity assays we demonstrated that early up-regulation of cytolytic genes was accompanied by acquisition of killing capacity within 24 hours of stimulation. However, T-cell proliferation was not observed until 48 hours. We therefore conclude that clonal expansion rather than acquisition of effector function is the rate-limiting step in the development of a primary CTL response.